2022
DOI: 10.1007/s00221-021-06258-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interhemispheric inhibition on bimanual movement control in young and old

Abstract: Interhemispheric interactions demonstrate a crucial role for directing bimanual movement control. In humans, a well-established paired-pulse transcranial magnetic stimulation paradigm enables to assess these interactions by means of interhemispheric inhibition (IHI). Previous studies have examined changes in IHI from the active to the resting primary motor cortex during unilateral muscle contractions; however, behavioral relevance of such changes is still inconclusive. In the present study, we evaluated two bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…Similarly, motor overflow observed during finger movement tasks has been reported to be caused by the increased activation of bilateral cerebral hemispheres with advancing age [34,35]. Recently, Morisita et al reported a relationship between interhemispheric inhibition and motor overflow using TMS [11]. In this study, 22 individuals were included in a group of young individuals with a mean age of 26.1 years and a group of elderly individuals with a mean age of 65.0 years.…”
Section: Motor Overflow In Elderly Individuals Is Primarily Treated A...mentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, motor overflow observed during finger movement tasks has been reported to be caused by the increased activation of bilateral cerebral hemispheres with advancing age [34,35]. Recently, Morisita et al reported a relationship between interhemispheric inhibition and motor overflow using TMS [11]. In this study, 22 individuals were included in a group of young individuals with a mean age of 26.1 years and a group of elderly individuals with a mean age of 65.0 years.…”
Section: Motor Overflow In Elderly Individuals Is Primarily Treated A...mentioning
confidence: 81%
“…However, recent studies have demonstrated a link between age-related alterations and interhemispheric inhibition [9]. Therefore, in the context of an increasingly elderly population worldwide, interhemispheric inhibition may serve as a predictive indicator of motor and cognitive decline in the elderly [9][10][11]. In this chapter, we review the latest assessment indices for interhemispheric inhibition and assessment methods for potential application in the clinical physiotherapy setting.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions are complex enough that bimanual cortical activations are not necessarily stronger than unimanual [26, 14]. The interhemispheric inhibition plays an important role in the control of bimanual movements [32, 21] Increasing evidence on participation of both cortical hemispheres in unilateral motion has led some researchers to speculate that unimanual motions are specific case of bimanual motions, where the opposing arm is inhibited [11, 6].…”
Section: Discussionmentioning
confidence: 99%